The Effect of Leadership Style and Employee Satisfaction on Employee Commitment of UMM Hospital Malang - Aditya Dharma Agung; Achmad Mohyi; Siti Nurhasanah (Universitas Muhammadiyah Malang, 2021)
This study aims to analyze the effect of job satisfaction and leadership style on the organizational commitment of employees at Muhammadiyah University Malang hospitals. This type of research is causal research, while data collection techniques are through questionnaires. The sampling technique uses the Probability Sampling technique, with 70 respondents. The analytical tool used is the Scale Range and Multiple Linear Regression. The results of the analysis note that the leadership style in the good category, job satisfaction in the category satisfaction, and organizational commitment in the high category. Leadership style has a positive and significant effect on organizational commitment. Job satisfaction has a positive and significant effect on organizational commitment. Situational leadership style and job satisfaction have a positive and significant effect on organizational commitment, this means that if the situational leadership style is getting better and job satisfaction is more satisfied, the organizational commitment of employees will be high